What does liberalization without price competition achieve?: The case of cocoa in Ghana - Vigneri, Marcella; Santos, Paulo (International Food Policy Research Institute, 2008)
The deregulation of Ghana’s domestic cocoa supply chain that took place in the early 1990s was expected to bring competition among different private buyers and to generate a number of production incentives to the farmers. Most notably, it was expected that competition would emerge by means of price bonuses and/or premiums over the guaranteed price. However, this paper finds that price-based competition mechanisms did not develop in the resulting domestic cocoa value chain. Rather, the now increasing numbers of Licensed Buying Companies compete for cocoa supplies based on the provision of different services to farmers. The availability of a number of outlets offers farmers the option to choose among those that can provide cash as well as credit. The cash payment and credit for inputs offered to attract cocoa sales mainly benefit liquidity-constrained farmers, enabling them to invest in productive inputs. Since cash constrained farmers are likely to be the poorest as measured by simple welfare indicators, liberalization may be seen to have had a progressive impact on Ghana’s cocoa farmers.